CONTINUAL QUALITY IMPROVEMENT OF ONLINE COURSE DELIVERY USING PERCEIVED COURSE LEARNING OUTCOMES - Thirumeni Subramaniam; Nur Amalina Diyana Suhaimi (2018)
The input from learners (as a key stakeholder) in the education sector is highly important and is a requirement in Total Quality Management or Continuous Quality Improvement (CQI). This is supported by Eom, Ashill and Wen (2006) who highlighted the use of perceived learning outcomes and satisfaction as the goals of educational outcomes in a distance delivery system that uses 3 computer-based instructional systems. Adult learners who are assumed to be self-directed learners ought to be responsible. Thus, they are the best judge over the impact of the delivery modes to their achievement of the learning outcomes.